Research Travelogue on Applications of Augmented Reality - Mrs. P.Menaka; M. Aishvariya Sri; U. S. Swetha (International Journal of Engineering and Management Research, 2021)
Augmented reality (AR) is an interactive experience of a real-world environment where the objects that reside in the real world are enhanced by computer-generated perceptual information, sometimes across multiple sensory modalities, including visual, auditory, haptic, somatosensory and olfactory.AR can be defined as a system that incorporates three basic features: a combination of real and virtual worlds, real-time interaction, and accurate 3D registration of virtual and real objects. This paper aims to provide an overview of current technologies and implementations of augmented reality as well as to describe the main application domains and outlining benefits. It also briefly describes about the powerful real time implementations of augmented reality and also its benefits.